The Simplicity of M. Natsir's Life: Character Education Values in the History of an Indonesian National Hero - Agus Susilo Saefullah; Naufal Al Zahra (UIN Fatmawati Sukarno Bengkulu, 2024)
The glamorous lifestyle of several top officials' families often attracts sharp public attention. This condition is very different from the previous national heroes who fought and provided examples to society when they became public officials. Therefore, this research explored the simplicity of the life of M. Natsir, an Indonesian national hero, by analyzing the values of character education reflected in the simplicity of his life. This research uses qualitative-descriptive methods and historical analysis, with data from various primary and secondary sources, including M. Natsir's biography, speeches and writings. The data was collected using a heuristic method, followed by a verification and interpretation process. Research findings show that the values of character education are manifested in M. Natsir's life, such as not being extravagant, rejecting gratification, and living as he is. These values can be seen in the way they dress, where they live and their lifestyle. These values are relevant in the current context of character education. This research concludes that the simplicity of M. Natsir's life has significant implications as an inspiration for Indonesia's young generation in building strong character and integrity. Apart from that, this research also emphasizes the importance of including the noble values of historical figures in the national education curriculum as an effort to form a nation with character.